ChemInform Abstract: Design of α‐Selective Glycopyranosyl Donors Relying on Remote Anchimeric Assistance. Issue 16 (March 2016) - Komarova, Bozhena S.; Tsvetkov, Yury E.; Nifantiev, Nikolay E.
Abstract: Review: 79 refs.